The most relevant academic areas in journals of education: a comparative analysis of Scimago’s rank (Papeles, 2016)
Scimago is the most relevant scientific journal ranking focused on determining the academic impact of these in their areas of study. This paper attempts to make a comparative analysis on the academic areas of the first 15 journals specialized on education, ranked by Scimago in the year 2014. This comparative approach states by the need to go into detail about the set of disciplines on which these documents were registered, and the question: what subjects are actually being investigated and published concerning the education? For this purpose, it is essential the analysis of three Colombian journals from the same education field. In order to achieve this goal, certain variables were selected (nationality, language, academic area determined by the journal and by its index, among others). Considering these variables, it could be found the existing connections and subsequently make comparisons between the bibliometric indicators within the specified category.
Keywords: journals of education; science teaching; bibliometric; Scimago; education